Calculation Experiment for Various Dynamics Types Electrical Installation Wires in Power Systems - I. I. Serguey; P. I. Klimkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents mathematical models and results of computer calculations on various types of low-frequency oscillation of wires. The proposed universal numerical method for calculation of wire dynamics is based on model of a wire in the form of flexible and elastic thread. While assigning combined boundary problems of wire dynamics a principle of mechanics links. Package of computer programs for calculation of electro-dynamic stability, dancing and sub-oscillations of electrical installation wires in power systems has been set up and evaluated.